Analisis Perbandingan Algoritma Elias Delta Code Dengan Algoritma Prefix Code Dalam Mengkompresi Data Teks - Kevin Yanto Sarumaha; Muhammad Syahrizal; Edward Robinson Siagian (STMIK Budi Darma, 2022)
The use of storage media to store various data, be it text, video or audio, has been used for a long time and continues to grow today. The amount of data will affect the process of data transmission and the use of large enough storage space. This is the background for applying the compression process to data, especially text data, so that data can be reduced and facilitate the data transmission process and use less storage space. However, many compression techniques or methods have been found from various experts, which makes it a difficult choice to determine which method is efficient enough for compressing data, especially text data. Data compression, of course, gives results from different compression ratios, including the Elias Delta Code and Prefix Code compression yahoo. In compressing text data the author uses the yahoo Elias Delta Code and yahoo Prefix Code compression methods and analyzes and compares the performance results of the data compression ratio in the two algorithms. In this study, comparisons were made in comparing the Elias Delta Code algorithm and the Prefix Code algorithm in text data compression, the Elias Delta Code algorithm topped first with a comparison result of 73.3% compared to the Prefix Code algorithm which had a comparison value of 66.6%. . Based on this analysis, the Elias Delta Code algorithm is the best algorithm for compressing.